(untitled) (The International Journal for Scientific Research, 2025)
The five hybrid tomato genotypes were investigated. Samples were obtained from disease- and insect-free young leaves; DNA was extracted with a Genomic DNA Mini Kit. The amount of DNA was determined by measuring the absorbency at 260 and 280 nm. The purity of the samples was 1.8–1.9, indicating isolation efficiency. Ten primers of RAPD from Operon Technology were initially applied among which five primers (A10, I14, A9, C13 and K01) produced good discriminative bands. Long distance polymerase chain reactions (PCR) were conducted with AccuPower® TLA PCR PreMix tubes, StCyclesY PCR was repeated 40 times here. The electrophoresis gel on 1.2% agarose was then run and the ethidium bromide-stained gel viewed under UV light the bands being noted. The results revealed that Different numbers of amplified bands were generated under the influence of primers. It presented primer K01, with the highest total number of bands (20 bands) and primer I14 with the lowest number of them (8 bands). In line with that, Prime C13 presented the highest amplification efficiency (100), and discriminatory power values of 10.4 which make it suitable to de- tect genetic variation among the genotypes studied. The efficiencies of primers were between 21.43 and 100%. Results showed that certain primers have a stronger affinity with repetitive sites in the genome to affect the detection of genetic variation. Genetic similarities showed a notable diversity among studied cultivars (0.24 to 0.51). This presented variability was of a genetic nature between the genotypes and indicated a medium to high genetic diversity. The varieties were grouped into two main clusters based on their genetic similarity and dependence from a common genetic background using the UPGMA analysis to generate a dendrogram.